ETNISITAS, HUBUNGAN SOSIAL DAN KONFLIK DI KALIMANTAN BARAT - Haba, John (P2KK LIPI, 2012)
Indonesia has more than 300 ethnic groups living scaterred in around 17.000 islands. Having said that, brilliantly Indonesian founding fathers such Soekarno, Hatta and other prominent leaders fought and struggled to lay down a very strong foundation, to bring all ethnic groups and its complexities into the one nation state. Since the beginning, the challenge is to bring all the ethnic groups, races, religious adherents together into one framework of thinking, that we are one nation being constructed from various social, ethnic and religious background. Various regional unrest during Soekarno’s era up to the present, should be discerned as a consequence of imbalance development policy and political ‘treatment’ especially over people who reside in outer islands. Although improvement and reorientation of development policies and programs have brought much changes for people who live far from Jakarta. But, the arrival of decentralization period which had started in January 1999, where the transferred of power from the center to the region resumed, some ethnic violents and clashes occurred. One among several ethnic tragedy happened in Indonesia, was the bloody Sangau Ledo and Sambas conflict that severely forced the Madura peoples to leave the West Kalimantan Province, a site they had resided for many years. After the uncertainty in the social and ethnic nexus among Madura, Dayak and Melayu peoples, as a result of the conflict, today the situation is gradually improving, and social interaction in the conflict sites is much developing to be better compared with the time when the clashes erupted.